Lateral scapular slide test and scapular mobility in volleyball players - Ozunlu, N.; Tekeli, H.; Baltaci, G. (Journal of Athletic Training, 2011)
Context: The stability of the scapula in relation to the entire moving upper extremity is the key in the throwing sequence. The importance of scapular positioning in volleyball players has been well documented in the literature, but no one has compared scapular positioning between volleyball players and sedentary people.